Voltage-dependent inactivation of a calcium channel. - Fox, A P (1981)
The inactivation of Ca currents in unfertilized eggs of the marine polychaete Neanthes arenaceodentata was investigated by using a voltage clamp technique. These Ca currents do not appear to be masked by other currents in the voltage range studied. Inactivation increased monotonically with increasing depolarization and occurred at potentials more negative than the inward Ca current. Currents elicited by depolarization at different Ca concentrations had approximately the same time course of inactivation, even though the size of the currents varied by almost an order of magnitude. There was complete inactivation in solutions containing Ca, Sr, or Ba (all permeant) for depolarizations beyond -30 mV absolute; the time course of the inactivation process was similar for all three permeant ions. Increasing depolarizations toward the expected equilibrium potential for Ca, Ba, or Sr did not produce any lessening of the inactivation. Thus, it appears that the inactivation seen in Neanthes eggs is a purely voltage-dependent phenomenon.